2018
DOI: 10.1007/s11892-018-1049-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of AMPK in Brown and Beige Adipose Tissue (BAT): Implications for Obesity, Insulin Resistance, and Type 2 Diabetes

Abstract: Ablation of AMPK in mouse adipocytes results in cold intolerance, a reduction in non-shivering thermogenesis in brown adipose tissue (BAT), and the development of non-alcoholic fatty liver disease (NAFLD) and insulin resistance; effects associated with a defect in mitochondrial specific autophagy (mitophagy) within BAT. The effects of a β3-adrenergic agonist on the induction of BAT thermogenesis and the browning of white adipose tissue (WAT) are also blunted in mice lacking adipose tissue AMPK. A specific AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 78 publications
3
127
0
Order By: Relevance
“…The ACE is critical in the generation of angiotensin II (AngII) [71], it plays the main role in the classic RAS pathway [72]. AMPK has been proved to associate with many kinds of diseases, for instance cardiovascular disease [9,63], metabolic syndrome [56,67], renal pathophysiology [73], and aging [44]. So there should be some association between ACE and AMPK.…”
Section: Ace and Ampkmentioning
confidence: 99%
“…The ACE is critical in the generation of angiotensin II (AngII) [71], it plays the main role in the classic RAS pathway [72]. AMPK has been proved to associate with many kinds of diseases, for instance cardiovascular disease [9,63], metabolic syndrome [56,67], renal pathophysiology [73], and aging [44]. So there should be some association between ACE and AMPK.…”
Section: Ace and Ampkmentioning
confidence: 99%
“…AMPK stimulates the catabolic pathways to generate ATP while conserving the remaining ATP by switching off the anabolic pathways [99]. AMPK stimulates energy expenditure [29,[100][101][102][103][104][105][106][107][108][109], which maintains normal body weight, insulin sensitivity and liver-metabolism [103,[110][111][112][113][114][115][116][117]. Deregulation of AMPK is observed in obesity, diabetes and other metabolic diseases [29,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115]117].…”
Section: Bone Marrow Stem Cellsmentioning
confidence: 99%
“…Conversely, AMPK inhibits fatty acid biosynthesis, lipogenesis, cholesterol synthesis and gluconeogenesis by modulating ACC, sterol regulatory element binding protein 1C (SREBP1C), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) and CREB-regulated transcription co-activator 2 (CRTC2) or forkhead box transcription factors (FoxO1), respectively [99]. Moreover, AMPK promotes adipose tissue browning mediated thermogenic energy expenditure [116]. For example, various agents like apelin, miRNA-455, resveratrol, cryptotanshinone, medicarpin and AICAR increase AMPK activity and adipocyte browning [116].…”
Section: Bone Marrow Stem Cellsmentioning
confidence: 99%
“…Therefore, the protein is a key therapeutic target for the treatment of major metabolic disorders including obesity and type-2 diabetes [103]. As adipogenesis is an energy consuming process, AMPK regulates the inhibition of expression of FAS, adipocyte specific pre-adipocytes, highlighting the potential role of AMPK in the inhibition of adipogenesis [111] In addition, AMPK has also been shown to be pertinent in the britening of WAT thereby increasing the energy expenditure through thermogenesis [112,113]. It has also been reported that the activity of AMPK increases during the differentiation of brown adipocytes and that targeting AMPK by short interfering RNAs (siRNAs), inhibits the differentiation of pre-adipocytes into mature brown adipocytes [16,114].…”
Section: Metabolic Functions Of Ampk and Role In Adipogenesismentioning
confidence: 99%
“…Upstream kinases of AMPK include Liver Kinase B1 (LKB1), mouse protein 25 (MO25) and STE-related adaptor (STRAD). LKB1[112,118], is part of a heterotrimeric protein.For activation, it needs the binding of other two upstream kinases of AMPK, STRAD and MO25 to form a heterotrimeric complex. It directly activates AMPK by phosphorylating Thr172 of α subunit.…”
mentioning
confidence: 99%